Peculiarities of Hardiness and Basic Beliefs of Women as Paternalistic Attitudes’ Factors in Economic Behavior - Shtryhol, Diana; Lamash, Iryna (Psychological Prospects Journal, 2016)
The article presents the results of theoretical and empirical studies of the hardiness and basic beliefs of women as paternalistic attitudes’ factors in economic behavior. Attitudes on economic paternalism reflect the hopes for the state in difficult economic circumstances, the expectations from the state a different kind of assistance that encourages passivity and evasion of personal moral responsibility. With respect to the relatively active studying of the several problems of economic consciousness and behavior the investigation of the psychological characteristics of socially unprotected women receiving social assistance from the state (i. e. implementing paternalistic economic attitudes) acquires relevance in today’s realities.Women with paternalistic economic attitudes have lower of the ability to withstand a stressful situation with maintaining the internal balance and without reducing the success of the activity. The low level of hardiness is due at the conviction that the involvement in an event offered a chance to find something worthwhile and interesting for them. They are increasingly experiencing their own helplessness. As a sense of what they independently choose their activities, their own way, and attempts to influence events have less inherent in these subjects. These women are less confident in the commitment and the justice of the world, in the goodness of people. They are less rely on luck, as well less likely to evaluate themselves as a decent person who is worthy of love and respect, are less confident in their own self-worth, an ability to control events that happen to them. This complex of psychological features is typical of the conditions of learned helplessness, reduced hardiness and tendency to psychological self – handicapping.